Enhanced C-band Coaxial Orthomode Transducer (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2014)
Introduction. In this paper a novel configuration of wideband coherent coaxial OMT is presented. General Design of an Orthomode Transducer. The OMT consists of elements of 3 main types: a turnstile junction between coaxial quad-ridged waveguide and 4 coaxial transmission lines; 4 coaxial transmission lines of LMR400 type; 2 antiphase power combiners/dividers. A Turnstile Junction Optimization. The optimization of a turnstile junction has been performed. Its minimized reflection coefficient is less than −28 dB in the operation frequency band 3.4–5.4 GHz. A Wideband Antiphase Power Combiner/Divider. The optimization of an antiphase power combiner/divider has been performed. Its minimized reflection coefficient is less than −38 dB. Characteristics of Coaxial Orthomode Transducer Developed. The simulation of OMT characteristics has been performed using CST Design Studio software. Conclusions. A wideband coherent coaxial orthomode transducer has been developed for the operation frequency band 3.4–5.4 GHz. In this frequency band the reflection coefficient of OMT is less than −24 dB and its crosspolar isolation exceeds 38 dB. The wideband coaxial OMT developed can be used in dual-polarized multiband antennas for satellite telecommunications and for radioastronomy.